Bioaccumulation of PCBs in liver tissue of dusky Carcharhinus obscurus, sandbar C. plumbeus and white Carcharodon carcharias sharks from south-eastern Australian waters. Issue 2 (30th December 2015) - Gilbert, Jann M.; Baduel, Christine; Li, Yan; Reichelt-Brushett, Amanda J.; Butcher, Paul A.; McGrath, Shane P.; Peddemors, Victor M.; Hearn, Laurence; Mueller, Jochen; Christidis, Les
Abstract: Polychlorinated biphenyls (PCBs) are ubiquitous pollutants in the marine environment that are known to accumulate in apex predators such as sharks. Liver samples from dusky Carcharhinus obscurus, sandbar Carcharhinus plumbeus, and white Carcharodon carcharias sharks from south-eastern Australian waters were analysed for the seven indicator PCBs 28, 52, 101, 118, 138, 153 and 180. Median ∑ PCBs were significantly higher in white than sandbar sharks (3.35 and 0.36 μg g − 1 lipid, respectively, p  = 0.05) but there were no significant differences between dusky sharks (1.31 μg g − 1 lipid) and the other two species. Congener concentrations were also significantly higher in white sharks. Significant differences in PCB concentrations between mature and immature dusky (3.78 and 0.76 μg g − 1 lipid, respectively) and sandbar (1.94 and 0.18 μg g − 1 lipid, respectively) sharks indicated that PCB concentrations in these species increased with age/growth. Higher-chlorinated congeners (hexa and heptachlorobiphenyls) dominated results, accounting for ~ 90% of ∑ PCBs. Highlights: PCBs were analysed in 11 sandbar, 11 dusky and 5 white sharks. Concentrations of PCBs were higher in higher trophic level species. PCB body burdens were different in different-sized individuals and some trends were observed. High concentrations in juvenile white sharks may suggest maternal transfer. Higher-chlorinated congeners dominated the results.